Recursos e capacidades geradores de vantagem competitiva na captação de clientes: um estudo em uma IES municipal - Ferreira, Renata Rodrigues (Universidade do Vale do Rio dos Sinos, 2023)
This work was based on customer acquisition and competitive advantage, considering the Resource-Based Vision (RBV). The research focused on resources and capabilities and the VRIO model, in addition to presenting an overview of higher education in Brazil, referring to the context of competitive advantage. In this sense, the work aimed to identify the resources and capabilities that proved to generate competitive advantage for attracting customers in a municipal Higher Education Institution. The work used qualitative exploratory-descriptive research, with semi-structured interviews to collect data. The data analysis technique used was content analysis for the study of higher education, including interviews with administrative staff and managers directly linked to client acquisition at the university analyzed. The work aimed to: describe the strategies that are competitive differentiators for an Instituição; identify the resources and capabilities mobilized by the IES in attracting customers; verify which resources and capabilities proved to be most strategic and led to an increase in the number of people enrolled in selection processes and an increase in the number of enrollments at the IES. The results indicate that, in attracting customers from the Higher Education Institution studied, the initial price reduction strategy proved to be an attraction factor, however, the turning point for competitive advantage resided, in fact, in the transition to an approach customer-centric. The synergy between resources and capabilities, when strategically combined and supported by supporting and complementary resources, emerges as the basis for boosting the institution's current performance. Finally, the study emphasizes that real differentiation is achieved not only through the possession of resources, but through their intelligent interconnection.
Keywords: Vantagem competitiva; Captação de clientes; Visão baseada em recursos; Instituições de ensino superior; Competitive advantage; Customer acquisition; Resource-based view; Higher education institutions; ACCNPQ::Ciências Sociais Aplicadas::Administração